A very personal crisis: Family fragilities and everyday conjunctures within lived experiences of austerity - Hall, Sarah M. (Transactions - Institute of British Geographers (1965), 2019)
This paper brings together key ideas from across economic and social theory to expand geographical understandings of crisis at the personal scale. Drawing on ethnographic research with families in Greater Manchester, UK, together with literatures on the geographies of crises and conjunctures, I argue that economic crises, such as austerity, can be revealing of the fragilities within familial and personal relationships and as such constitute a very personal crisis. In times of austerity and economic crisis, questions are raised about how people imagine themselves, and the relationships, spaces, and times in which they situate their lives - previously, presently, and prospectively. I advance conceptualisations of the ways austerity and economic crisis "play out" to illustrate how everyday life is punctuated and disrupted by crises and conjunctures of various types. Personal conditions of austerity are knotted within personal inventories of important life experiences, relational comparators, and memories, of social, emotional, or financial hardship, which resonate strongly. Furthermore, I identify the way in which crises are woven within imaginarles of the future, personal biographies, and lifecourse trajectories, whereby economic crises and austerity can be felt as life crises. Providing added depth to current geographical literature focused on the personal scale, in this paper economic crises and austerity are shown to be personally affective, having lasting impacts on social relationships. Ultimately, I make the case for how an economic crisis is almost always and inevitable felt as a personal crisis; a vital conjuncture, the crescendo of circumstance, opening up the sores of memories and creating new ones, compromising familial and financial fragility.